Coming home [videorecording (DVD)] - Ashby, Hal; Fonda, Jane, 1937-; Voight, Jon, 1938-; Dern, Bruce; Carradine, Robert, 1954- (MGM/UA Home Video, 2002)
A love story set against the social upheaval of the Vietnam war. While Sally's husband is serving in Vietnam, she becomes involved with a veteran of the war, a paraplegic at a San Diego veterans hospital.